Educação para a cidadania: a autonomia em Kant e Freire - Muzzatto, Egidiane Michelotto (2017)
The objective of this study is to propose an alternative of education for citizenship and autonomy in contemporaneity from educational theories of Immanuel Kant (1724 – 1804) and Paulo Freire (1921 – 1997). Based on the assumption that, for having equal living conditions, it’s necessary that society is composed by enlightened, critic and active individuals. For this reason, human education must be invested in, based on the understanding and exercise of autonomy. Without autonomy there is no human promotion, but rather heteronomy, oppression and passivity. This way, situated on different physical and chronological contexts, one in the 18th and the other in the 20th centuries, Kant and Freire understand that education is a necessary instrument for human development and it happens continuously, throughout life, in theoretic and practical areas. Kant concluded that human beings aren’t born moral, but become moral. In doing so, instruction aims to promote the adequate use of reason, understood as superior to instincts. Thereby, acting in an autonomous manner both external and internally, the individual becomes free, achieves enlightenment. Engaged in social movements, Freire developed a pedagogical archetype that conceives the human person in its totality, inserted in a spatial, cultural and temporal context. Education is, therefore, an activity towards and together with the social, political and anthropological. Thus, education’s function is to prepare individuals to concretely read the world, understanding the dynamic of relations, indicating situations of heteronomy, bringing changes to personal and collective conjunctures. The aspects defended by Kant and Freire provide elements for an education for contemporaneity. It is known that this century’s citizen differs from the citizen of the late 20th Century. Thus, education also has to be different. Teaching technics is not enough, there must be education for the concreteness of life, aggregating ethical, esthetic and moral values to formation. Therefore, an able individual for challenges: a citizen. As a result, the proposal for this century’s beginning is the education towards democratic citizenship. Understood as an educational system that prepares for life’s integrality, it is developed based on three fundamental points in academic curriculums: universal citizenship, critical thinking and narrative imagination (NUSSBAUM, 2015). Therefore, besides the main thinkers, the following authors are taken as references: Rousseau (1999), Canivez (1991), Carvalho (2008), Covre-Manzini (1991), Dalbosco (2011), Dubet (2011), Flickinger (2004), Giddens (2002), Hall (2003), Marshall (1967), Nodari (2011), Palma Filho (1998), Reale e Antiseri (2004), Romanelli (1999), Zatti (2007) e Nussbaum (2015). This way, methodologically based on Gadamerian hermeneutics, this thesis aims on approaching the historical aspects of citizenship, autonomy and education; of Kantian educational philosophy and Freirean pedagogy; and lastly, the possibility of facing the challenges of this time: an education for democratic citizenship.